2011
DOI: 10.1007/s12031-011-9648-6
|View full text |Cite
|
Sign up to set email alerts
|

Brain Expression of Kv3 Subunits During Development, Adulthood and Aging and in a Murine Model of Alzheimer’s Disease

Abstract: In neurons, voltage-dependent Kv3 potassium channels are essential for the generation of action potentials at high frequency. A dysregulation of the Kv3.1 and Kv3.4 channel subunits has been suggested to contribute to neuronal and glial alterations in Alzheimer's disease, but a quantitative evaluation of these subunits in a mouse model of the pathology is still lacking. We analysed the profile of expression of the four Kv3 subunits by quantitative reverse transcription PCR and Western blot in the whole mouse b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…, Epha4 [40], Scn1a [41], and Kcnc1 [42]. Protein detection by immunoblot was used to validate some of the microarray gene expression data with different cohorts of mice.…”
Section: Resultsmentioning
confidence: 99%
“…, Epha4 [40], Scn1a [41], and Kcnc1 [42]. Protein detection by immunoblot was used to validate some of the microarray gene expression data with different cohorts of mice.…”
Section: Resultsmentioning
confidence: 99%
“…They demonstrated that highly elevated ROS levels are found in the aging brain and in many neurodegenerative diseases and therefore, oxidative modification of K + channels might be a general principle underlying aging and neurodegeneration 56 . Kv3.4 has been suggested as a new therapeutic target for major neurodegenerative diseases, and the mechanisms of Kv3.4 related to these diseases have been investigated 14, 57 . However, the relationship between the oxidative modification of Kv3.4 and neurodegenerative diseases remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of gene expression throughout the different stages of AD suggests that up-regulation of Kv3.4 (KCNC4) and dysregulation of Kv3.1 (KCNC1) alter potassium currents in neurons and leads to altered synaptic activity that may underlie the neurodegeneration observed in AD (165). While in contrast, in the neocortex of aged APPPS1 mice, Kv3.1 mRNA and protein levels were significantly lower compared to wild type, suggesting that a decrease in Kv3 currents could play a role in the cognitive symptom s of Alzheimer 's disease (166). While in contrast, in the neocortex of aged APPPS1 mice, Kv3.1 mRNA and protein levels were significantly lower compared to wild type, suggesting that a decrease in Kv3 currents could play a role in the cognitive symptom s of Alzheimer 's disease (166).…”
Section: Neuronal Diseasesmentioning
confidence: 99%